Associação entre os polimorfismos do gene BCMO1 (β-caroteno 15,15'-monooxigenase 1) e as concentrações séricas de β-caroteno e retinol em diferentes etnias brasileiras - Santos, Vanessa Lorenço Peresi dos [UNESP] (2015)
Vitamin A is important in human nutrition, since deficiency is considered a serious public health and child mortality. Provitamin A carotenoids, particularly β-carotene from certain plant foods are important sources of vitamin A for many populations. During the bioconversion process carotenoids are cleaved by cytosolic enzyme β-carotene 15,15'-monooxygenase 1 (BCMO1). Two polymorphisms (Single Nucleotide Polymorphisms - SNPs) in BCMO1 gene, R267S: rs12934922 and A379V: rs7501331, were identified in ethnic populations of Caucasian, Japanese and Chinese, and it may cause reduced enzyme activity BCMO1 and justify the wide inter-individual differences in bioconversion of β-carotene into vitamin A. The aims of this study were to identify the frequency of polymorphic variants A379V and R267S/A379V of BCMO1 gene in three population groups (whites, blacks and Japanese) and evaluate the relationship between SNPs with serum β-carotene and retinol among three different ethnic groups. Each group was composed of 100 volunteers, with European, African and Japanese ancestry, and 50% were female and 50% male. Were evaluated plasmatic concentrations of β-carotene, retinol, zinc erythrocyte, lymphocytes, C-reactive protein, α-1-acid glycoprotein and dietary intake of Vitamin A. Samples of saliva and oral mucosa exfoliated cells were collected for DNA extraction with subsequent genotyping of SNPs R267S: rs12934922 and A379V: rs7501331 by RT-PCR. The frequencies of allelic variants R267S and A379V at least one T allele for individuals with European ancestry were 63.0% and 44.0%, respectively, African ancestry, 48.0% and 18.0%, respectively, and Japanese ancestry, 21.0 % and 27.0%, respectively. The results show, so unique, that the frequencies of polymorphic variants of the polymorphic variants A379V and R267S BCMO1 gene in Brazilian population groups evaluated depend on ethnicity for both SNPs. The polymorphic variants observed do not seem to ...